2018
DOI: 10.1097/md.0000000000011132
|View full text |Cite
|
Sign up to set email alerts
|

Anterior mediastinal leiomyosarcoma mimicking thymoma

Abstract: Rationale:Mediastinal leiomyosarcoma is very rare. In this paper, we report one case of anterior mediastinal leiomyosarcoma and retrospectively review the imaging findings of previously reported cases.Patient Concerns:A 61-year-old male patient was admitted to our hospital due to the presence of a mediastinal space-occupying lesion for two years. Two years previously, chest computed tomography (CT) showed a small nodule in the anterior mediastinum. Twenty days previously, the CT examination was repeated at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Primary mediastinal sarcomas are mostly derived from mediastinal organs, such as the heart, esophagus, and the blood vessels. Only 7 cases of anterior mediastinal leiomyosarcomas have been reported [7-10]. Here, we report an extremely rare case of anterior mediastinal leiomyosarcoma in an 85-year-old female.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Primary mediastinal sarcomas are mostly derived from mediastinal organs, such as the heart, esophagus, and the blood vessels. Only 7 cases of anterior mediastinal leiomyosarcomas have been reported [7-10]. Here, we report an extremely rare case of anterior mediastinal leiomyosarcoma in an 85-year-old female.…”
Section: Introductionmentioning
confidence: 81%
“…Mediastinal leiomyosarcoma is a very rare tumor with less than 50 cases reported as case reports and a few small case series [7-13]. This tumor occurs typically in the posterior mediastinum [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that foreign bodies such as bullets, laparotomy sponges, and bone wax may be associated with sarcoma causes, but the exact mechanisms are unclear[ 18 , 19 ]. Initial primary mediastinal leiomyosarcoma symptoms lack specificity and depend on the tumor location[ 1 , 2 , 10 , 20 , 21 ]. Posterior mediastinal tumors often do not cause obvious clinical symptoms and discomfort in the early stage[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A leiomyosarcoma is an aggressive malignant tumor that originates in the mesenchymal tissue (2). Mediastinal leiomyosarcomas mostly occur in mediastinal organs, such as the heart, great vessels, and esophagus, usually manifesting as posterior mediastinal tumors, and rarely as anterior mediastinal tumors (3). Only few cases of anterior mediastinal leiomyosarcomas have been reported to date (3).…”
Section: Introductionmentioning
confidence: 99%